Activation of Placental mTOR Signaling and Amino Acid Transporters in Obese Women Giving Birth to Large Babies - Jansson, Nina (Endocrine Society, 2013)
CONTEXT: Babies of obese women are often large at birth, which is associated with perinatal complications and metabolic syndrome later in life. The mechanisms linking maternal obesity to fetal overgrowth are largely unknown. OBJECTIVE: We tested the hypothesis that placental insulin/IGF-I and mammalian target of rapamycin (mTOR) signaling is activated and amino acid transporter activity is increased in large babies of obese women. DESIGN AND SETTING: Pregnant women were recruited prospectively for collection of placental tissue at a university hospital and academic biomedical center. PATIENTS OR OTHER PARTICIPANTS: Twenty-three Swedish pregnant women with first trimester body mass index ranging from 18.5 to 44.9 kg/m(2) and with uncomplicated pregnancies participated in the study. INTERVENTIONS: There were no interventions. MAIN OUTCOME MEASURES: We determined the phosphorylation of key signaling molecules (including Akt, IRS-1, S6K1, 4EBP-1, RPS6, and AMPK) in the placental insulin/IGF-I, AMPK, and mTOR signaling pathways. The activity and protein expression of the amino acid transporter systems A and L were measured in syncytiotrophoblast microvillous plasma membranes. RESULTS: Birth weights (range, 3025–4235 g) were positively correlated to maternal body mass index (P < 0.05). The activity of placental insulin/IGF-I and mTOR signaling was positively correlated (P < 0.001), whereas AMPK phosphorylation was inversely (P < 0.05) correlated to birth weight. Microvillous plasma membrane system A, but not system L, activity and protein expression of the system A isoform SNAT2 were positively correlated to birth weight (P < 0.001). CONCLUSIONS: Up-regulation of specific placental amino acid transporter isoforms may contribute to fetal overgrowth in maternal obesity. This effect may be mediated by activation of insulin/IGF-I and mTOR signaling pathways, which are positive regulators of placental amino acid transporters.